Food Policy Councils as Loci for Practising Food Democracy? Insights from the Case of Oldenburg, Germany - Sieveking, Annelie (2019)
In the highly concentrated and consolidated 21st century food systems, a broad range of stakeholders are rarely involved in food-related decision-making processes. One innovative institutional response is the establishment of food policy councils (FPCs). These institutions are often initiated by civil society actors and seek to transform prevailing agro-industrial food systems. They aim to raise awareness for alternative practises of food consumption and production, and they try to shape food policies at different governance levels. FPCs have been acclaimed for their democratic potential in the past. This study uses the five key dimensions of food democracy identified by Hassanein (2008) to assess the ways in which FPCs might represent loci for practising food democracy. This is achieved by taking one of the first FPCs in Germany as an example. During a two-year study period (2016–2018), the emergence of the FPC Oldenburg was studied through participant observations, semi-structured interviews, and document analysis. Data analysis reveals examples of, as well as challenges related to, all five dimensions of food democracy. In addition, the in-depth analysis of the case also illustrates the importance of taking additional aspects into account, i.e., openness and transparency. Looking at an additional dimension of food democracy, which covers the “How?” of the deliberative process, might allow for a more nuanced analysis of the democratic potential of food initiatives in the future.